2011
DOI: 10.1002/hep.24414
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen in primary biliary cirrhosis: An old story now reviving

Abstract: Primary biliary cirrhosis (PBC) is an autoimmune biliary disease characterized by injury of small and medium size bile ducts eventually leading to liver cirrhosis and death. While the causes remain enigmatic, recent evidence has strengthened the importance of genetic factors in determining the susceptibility to the disease. Besides the strong heritability suggested by familial occurrence and monozygotic twins concordance, for decades there has not been a clear association with specific genes, with the only exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 80 publications
3
46
0
1
Order By: Relevance
“…HLA allele determines the structure of the antigenbinding site and the specific characteristics of each expressed HLA molecule (HLA class I, A, B, Cw; HLA class II, DR, DQ and DP), thereby acting as a determinant of both susceptibility and resistance of autoimmunity [26][27][28][29] . Similar to many other autoimmune diseases, HLA has been extensively studied in PBC.…”
Section: Geneticsmentioning
confidence: 99%
“…HLA allele determines the structure of the antigenbinding site and the specific characteristics of each expressed HLA molecule (HLA class I, A, B, Cw; HLA class II, DR, DQ and DP), thereby acting as a determinant of both susceptibility and resistance of autoimmunity [26][27][28][29] . Similar to many other autoimmune diseases, HLA has been extensively studied in PBC.…”
Section: Geneticsmentioning
confidence: 99%
“…Given the high polymorphism of the hla complex, finding the same phenotype in multiple individuals is very rare, and thus hla has become an important target in the investigation of many diseases, including autoimmune, infectious, and malignant diseases, among others [25][26][27][28] . High expression of hla-dr is a marker of T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those different clinical characteristics, such as bone proliferation in enthesis site and sacroiliitis, in AS patients from those of patients with rheumatoid arthritis, AS is also known for its high association with HLA-B27. It has been known for more than 30 years since this association was discovered at 1973 (Schlosstein, 1973;Brewerton et al, 1973), although afterward, researchers found several HLA antigens were associated with other diseases (Invernizzi, 2011;McElroy, 2011;Piga, 2011), the strongest of any HLA antigens associated with human disease is HLA-B27 molecule. Hence, the roles of HLA-B27 in the pathogenesis and clinical manifestation of ankylosing spondylitis were among most frequent discussed topics in the past three decades.…”
Section: Introductionmentioning
confidence: 99%